Clinical performance of CAD/CAM all-ceramic tooth-supported fixed dental prostheses: a systematic review and meta-analysis - Saravi, Babak Ebrahimzadeh; Vollmer, Andreas; Hartmann, Maja; Lang, Gernot Michael; Kohal, Ralf-Joachim; Boeker, Martin; Patzelt, Sebastian B. M. (Materials, 2021)
Although CAD/CAM ceramics present a promising alternative to metal-ceramic fixed dental prostheses, little is known about their mid- and long-term clinical performance. This systematic review aims to estimate the survival and success rates and describes the underlying complication characteristics for CAD/CAM tooth-supported zirconia- and lithium disilicate-based fixed dental prostheses (FDPs). We systematically searched MEDLINE and Web of Science to find relevant prospective studies with a follow-up of at least one year. We estimated pooled 1-, 5-, and 10-year survival and success rates by combining the collected data in a Poisson regression model. Descriptive statistics were conducted to evaluate the distribution of failures and complications in the included studies. Risk of bias for the included studies was assessed with an adapted checklist for single-arm trials. Pooled estimated 1-, 5-, and 10-year survival rates ranged from 93.80% to 94.66%, 89.67% to 91.1%, and 79.33% to 82.20%, respectively. The corresponding success rates excluding failures, but including any other types of intervention were 94.53% to 96.77%, 90.89% to 94.62%, and 81.78% to 89.25%. Secondary caries was the most frequent cause of failure, followed by chipping of the veneering. The most common cause of complication excluding failures but requiring intervention was chipping of the veneering. Risk of bias was generally acceptable for the included studies, with seven studies associated with low risk of bias, eight studies with a moderate risk of bias, and three studies with serious risk of bias. The current meta-analysis on CAD/CAM-supported FDPs revealed satisfying survival and success rates for up to 10 years of exposure. More prospective studies focusing on long-term performance are needed to strengthen the evidence currently available in the literature.
Gesehen am 03.09.2021